Sistem Monitoring Penyiraman Otomatis Tanaman Bunga Gemitir Menggunakan Aplikasi Mobile dan Web Thingspeak - Sutama, I Wayan; Gama, Adie Wahyudi Oktavia; Negara, I Gede Artha; Wisesa, I Dewa Putu Arjun Suhartana (Universitas Pendidikan Nasional, 2021)
The role of technology is very important in an automatic watering monitoring system that works based on the YL69 sensor and DHT11 sensor. This study aims to determine the working principle of sensors in a plant watering monitoring system with mobile applications (Blynk) and thingspeak web. Thingspeak web design aims to process data recording. To process and dispatch YL69 sensor data and DHT11 sensor, the Arduino UNO microcontroller is used as well as a relay as a switch to drain and disconnect the electric current to the water pump. The design results show that this automatic plant watering monitoring system can work well, where the soil moisture is below <50%, the water pump will live